A Novel Laser Vaccine Adjuvant Increases the Motility of Antigen Presenting Cells - Chen, Xinyuan (Public Library of Science, 2010)
BACKGROUND: Development of a potent vaccine adjuvant without introduction of any side effects remains an unmet challenge in the field of the vaccine research. METHODOLOGY/PRINCIPAL FINDINGS: We found that laser at a specific setting increased the motility of antigen presenting cells (APCs) and immune responses, with few local or systemic side effects. This laser vaccine adjuvant (LVA) effect was induced by brief illumination of a small area of the skin or muscle with a nondestructive, 532 nm green laser prior to intradermal (i.d.) or intramuscular (i.m.) administration of vaccines at the site of laser illumination. The pre-illumination accelerated the motility of APCs as shown by intravital confocal microscopy, leading to sufficient antigen (Ag)-uptake at the site of vaccine injection and transportation of the Ag-captured APCs to the draining lymph nodes. As a result, the number of Ag(+) dendritic cells (DCs) in draining lymph nodes was significantly higher in both the 1° and 2° draining lymph nodes in the presence than in the absence of LVA. Laser-mediated increases in the motility and lymphatic transportation of APCs augmented significantly humoral immune responses directed against a model vaccine ovalbumin (OVA) or influenza vaccine i.d. injected in both primary and booster vaccinations as compared to the vaccine itself. Strikingly, when the laser was delivered by a hair-like diffusing optical fiber into muscle, laser illumination greatly boosted not only humoral but also cell-mediated immune responses provoked by i.m. immunization with OVA relative to OVA alone. CONCLUSION/SIGNIFICANCE: The results demonstrate the ability of this safe LVA to augment both humoral and cell-mediated immune responses. In comparison with all current vaccine adjuvants that are either chemical compounds or biological agents, LVA is novel in both its form and mechanism; it is risk-free and has distinct advantages over traditional vaccine adjuvants.